Ultrasonic study of the elastic properties of propylene glycol oligomers in the glassy state and during the glass–liquid transition. (3rd September 2022) - Danilov, Igor V.; Gromnitskaya, Elena L.; Brazhkin, Vadim V.
ABSTRACT: Using an ultrasonic technique under pressure, we investigated the dependence of elastic properties of propylene glycol, dipropylene glycol and tripropylene glycol on the concentration of hydrogen bonds and the mass of molecules. Studies were carried out up to 1.8 GPa in the glassy state and at isobaric heating during the glass–liquid transition. Propylene glycol in glassy state has the highest modules, and its interaction potential is more central than in di- and tripropylene glycol. Both the shear modulus G and the bulk modulus B are practically identical for glassy di- and tripropylene glycol.